An idea for compensating local farmers for a sustainable method of pineapple farming - Daud, Adrian; Taasim, Shairil Izwan; Rosli, Anita (Human Resource Management Academic Research Society, 2021)
Agricultural activities have the share in contributing to greenhouse gases in the atmosphere. The method of residue burning (RB), which has been practiced in Samarahan, Sarawak in Malaysia contributed to the emission of carbon into the atmosphere. Steps should be taken to address this issue by promoting sustainable method of farming. Pineapple farmers can be given incentives to change to a more sustainable method such as zero burning (ZB) whereby a mechanism like the clean development mechanism (CDM) can be adopted at the local level to encourage farmers adopting this sustainable farming technique. This incentive is primarily derived from the value of carbon sequestered in the soil through the practice of ZB. Although farmer will suffer financial loss due to additional cost, they can be compensated for this loss under ZB. Thus, farmers still can receive better income with the compensation and at the same continuing to practice ZB.